SEARCH FOR MEANING OF LIFE IN KATHRYN BIGELOW’S THE HURT LOCKER MOVIE (2009): AN EXISTENTIALIST CRITICISM - Adiyatma, Yoga Imam Bagus (2011)
This study is aimed to show the search for meaning of life in The Hurt Locker movie by using existentialist criticism. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the existentialist analysis. This research is descriptive qualitative research. Type of data of the study is image and text taken from two data sources: primary and secondary. The primary data source is the film and manuscript of The Hurt Locker movie directed by Kathryn Bigelow released in 2009. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound, and editing are related to each other and form the unity. Second, based on the existentialist analysis, Kathryn Bigelow wants to convey a moral message that war is a drug which a person will find meaning of life by undergoing a dangerous adrenaline. This movie also criticizes the rush of battle which is often a potent and lethal addiction, for war is a drug.